Statistical thinking frameworks and models comparative study in global models - Nashaat Abdelaziz, Abdelqader Baioumy; Ashraf, Mohamed Nemrawi (2019)
The current study aims to trace and analyze statistical thinking frameworks of various types in terms of their origin, types, dimensions, tasks, skills focused on them, hierarchy and sequence of levels, their theoretical and educational reference, The use of technology in its construction and the possibility of integration between all different statistical thinking frameworks or the construction of new frameworks. It relied on the inductive method in the survey of literature, studies and scientific reports that monitored the frameworks of statistical thinking. It also adopted the descriptive approach in analyzing and concluding the relationship between different statistical thinking frameworks Comparing and categorizing them , The most important results of the study that emerged from the frameworks of statistical thinking is different from the educational, statistical or commercial, etc., and most of the frameworks are one-dimensional and a few of them are two-dimensional, and the majority focused on the use of practical issues or tasks to reveal the levels of statistical thinking of learners, Computational thinking within the framework of statistical thinking, he study concluded several conclusions and recommendations. The most prominent of these was that the recent statistical thinking frameworks did not receive such global attention, despite their importance. However, the study recommended the need to increase attention to the frameworks of statistical thinking by developing them and to find a mechanism for integration among them or to build new statistical thinking frameworks.